SETTINGS OF INNATE AND JOINT ASSETS IN DIVORCE CASE BY LAW NUMBER 1 OF 1974 OFMARRIAGE IN THE IMPLICATIONS OF RELIGIOUS COURTS DECISION CLASS IA OF BENGKULU CITY NUMBER: 0289/PDT.G/2016/PA.BN - Widya Eka Putri; Akhmad Muslih; Adi Bastian Salam (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
Marriageraisesrights and obligations to husband and wife. The rights and obligations existing before the divorce are created from their marriage ceremony. The rights and obligations are contained in the provisions of Qur’an. To avoid conflict divorce is not an easy thing, it is motivated by several factors that cause a domestic relations be cracked even ended in divorce. The purpose of this research is to understand and analyze the factors that hinder the provision of livelihood to the former wife in divorce cases through decision of Manna Religious Court of South Bengkulu. Analyzing theproblems in this study, researchers used a analysis descriptive method to produce the research results showingfactors that inhibit the provision of livelihood to the former wife in divorce cases through decision of Manna Religious Court of South Bengkulu consisted of internal and external factors.